Evolution of Neuroplasticity in Response to Physical Activity in Old Age: The Case for Dancing - Müller, Patrick; Rehfeld, Kathrin; Schmicker, Marlen; Hökelmann, Anita; Dordevic, Milos; Lessmann, Volkmar; Brigadski, Tanja; Kaufmann, Jörn; Müller, Notger G. (Frontiers in Aging Neuroscience, 2017)
From animal research, it is known that combining physical activity with sensory enrichment has stronger and longer-lasting effects on the brain than either treatment alone. For humans dancing has been suggested to be analogous to such combined training. Here we assessed whether a newly designed dance training program that stresses the constant learning of new movement patterns is superior in terms of neuroplasticity to conventional fitness activities with repetitive exercises and whether extending the training duration has additional benefits. Twenty-two healthy seniors (63-80 y) who had been randomly assigned to either a dance or a sport group completed the entire 18-month study. MRI, BDNF and neuropsychological tests were performed at baseline and after 6 and 18 months of intervention. After 6 months, we found a significant increase in gray matter volume in the left precentral gyrus in the dancers compared to controls. This neuroplasticity effect may have been mediated by the increased BDNF plasma levels observed in the dancers. Regarding cognitive measures, both groups showed significant improvements in attention after 6 months and in verbal memory after 18 months. In addition, volume increases in the parahippocampal region were observed in the dancers after 18 months. The results of our study suggest that participating in a long-term dance program that requires constant cognitive and motor learning is superior to engaging in repetitive physical exercises in inducing neuroplasticity in the brains of seniors. Therefore, dance is highly promising in its potential to counteract age-related gray matter decline.